2018
DOI: 10.3389/fbioe.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid Formation by Clostridium ljungdahlii at Elevated Pressures of Carbon Dioxide and Hydrogen

Abstract: Low productivities of bioprocesses using gaseous carbon and energy sources are usually caused by the low solubility of those gases (e.g., H2 and CO). It has been suggested that increasing the partial pressure of those gases will result in higher dissolved concentrations and should, therefore, be helpful to overcome this obstacle. Investigations of the late 1980s with mixtures of hydrogen and carbon monoxide showed inhibitory effects of carbon monoxide partial pressures above 0.8 bar. Avoiding any effects of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Several resident and circulating cell types can undergo osteogenic differentiation/transdifferentiation upon osteogenic stimulation and, therefore, can be involved in vascular calcification. These cells include vascular smooth muscle cells (VSMCs), smooth muscle- and endothelial cell progenitors, pericytes, and adventitial cells, as well as circulating mesenchymal and hematopoietic stem cells [ 39 ]. In this review, we will focus on osteogenic/osteochondrogenic transdifferentiation of VSMCs because this is the most extensively studied mechanism and the most widely accepted theory to explain vascular calcification.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Several resident and circulating cell types can undergo osteogenic differentiation/transdifferentiation upon osteogenic stimulation and, therefore, can be involved in vascular calcification. These cells include vascular smooth muscle cells (VSMCs), smooth muscle- and endothelial cell progenitors, pericytes, and adventitial cells, as well as circulating mesenchymal and hematopoietic stem cells [ 39 ]. In this review, we will focus on osteogenic/osteochondrogenic transdifferentiation of VSMCs because this is the most extensively studied mechanism and the most widely accepted theory to explain vascular calcification.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Wood-Ljungdahl pathway for the synthesis of other chemicals (Oswald et al, 2018). Therefore, the chemical could be used as substrate by other formate consuming bacteria species attached to the biocathode after generation.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…Understanding the effects of different gases on LGS fermentation processes is crucial in optimizing gas compositions to achieve a desired product range. In fermenter-scale experiments, the influence of an increased headspace pressure was evaluated [108,[148][149][150]. Oswald et al demonstrated that an increase in pressure of up to 7 bar for LGS fermentations with C. ljungdahlii growing solely on CO 2 and H 2 led to a shift in the product spectrum [149].…”
Section: Respiration and The Challenge In Limited Gas-liquid Mass Tramentioning
confidence: 99%
“…Additionally, methanol and formate can be produced in LGS fermentation (Fig. 1, M and N) [95,149]. Methanol is considered a key molecule in methane-based biorefinery [95].…”
Section: Methanol and Formate As Universal Building Blocksmentioning
confidence: 99%